2017
DOI: 10.1038/srep40729
|View full text |Cite
|
Sign up to set email alerts
|

Integrated molecular analysis reveals complex interactions between genomic and epigenomic alterations in esophageal adenocarcinomas

Abstract: The incidence of esophageal adenocarcinoma (EAC) is rapidly rising in the United States and Western countries. In this study, we carried out an integrative molecular analysis to identify interactions between genomic and epigenomic alterations in regulating gene expression networks in EAC. We detected significant alterations in DNA copy numbers (CN), gene expression levels, and DNA methylation profiles. The integrative analysis demonstrated that altered expression of 1,755 genes was associated with changes in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 100 publications
0
15
0
Order By: Relevance
“…Lastly, we focused on those TFs that had been previously linked to RAS signaling (Cebpα, Cebpβ, Cmyb, Evi1, Meis1, The similar expression pattern of Gata3 and miR181a/miR181b, and the presence of regulatory elements in the Mir181ab1 promoter suggested that miR181a1 and miR181b1 could be regulated by Gata3. To substantiate this potential association, further analysis of GATA3 expression was done in immortalized lung epithelial cells expressing Gata2, Gata3, and Foxa2) (51)(52)(53)(54)(55)(56)(57)(58). Quantitative PCR (qPCR) analysis of the TFs revealed upregulation of Gata3 in both mouse lung and pancreatic cancer cell lines after TGF-β treatment for 3 hours ( Figure 9C), while no consistent upregulation in the 2 cell lines was found for the remaining TFs (Supplemental Figure 6, C and D).…”
Section: Resultsmentioning
confidence: 95%
“…Lastly, we focused on those TFs that had been previously linked to RAS signaling (Cebpα, Cebpβ, Cmyb, Evi1, Meis1, The similar expression pattern of Gata3 and miR181a/miR181b, and the presence of regulatory elements in the Mir181ab1 promoter suggested that miR181a1 and miR181b1 could be regulated by Gata3. To substantiate this potential association, further analysis of GATA3 expression was done in immortalized lung epithelial cells expressing Gata2, Gata3, and Foxa2) (51)(52)(53)(54)(55)(56)(57)(58). Quantitative PCR (qPCR) analysis of the TFs revealed upregulation of Gata3 in both mouse lung and pancreatic cancer cell lines after TGF-β treatment for 3 hours ( Figure 9C), while no consistent upregulation in the 2 cell lines was found for the remaining TFs (Supplemental Figure 6, C and D).…”
Section: Resultsmentioning
confidence: 95%
“…More crucially, it can provide novel insight leading to early diagnosis, definitive treatment, and survival prediction [ 12 ]. Previous research in the bioinformatics field has yielded some achievements in ESCA knowledge, such as identification of associated genes and pathways and altered methylation associated with ESCA pathology [ 13 , 14 ]. However, analytical ability for ESCA has been limited due to insufficient sample size and a lack of in-depth evaluation of key genes which play a dominant role in the malignant development of ESCA.…”
Section: Introductionmentioning
confidence: 99%
“…The gene expression profiles of GSE92396, contributed by Peng et al ( 11 ), were downloaded from the Gene Expression Omnibus (GEO) database ( ). The platform was GPL6244, HuGene-1_0-st Affymetrix Human Gene 1.0 ST Array.…”
Section: Methodsmentioning
confidence: 99%